Evaluation of growth patterns and maternal traits of Brakmas and Bali cows - Abd Wahab, Mohd. Hafiz (2015)
Evaluation of animals performance including growth and reproduction are very important to the animal breeders as it will be the turning point of gaining profit or loss in livestock enterprises. To ensure the sustainability of a livestock operation, the animals must be evaluated and selected properly. However, the evaluation process especially on animals‟ growth often took a longer period; therefore the use of nonlinear algebraic models is the best way to evaluate the growth event of the animals as it summarized the entire life data point into several biologically interpretable parameters. The objectives of the study were to determine the best non-linear model to describe the growth pattern of Brakmas and Bali cows and to compare the maternal traits of these two breeds. Four non-linear growth models namely Gompertz, von Bertalanffy, Brody and Logistic were used to determine the asymptotic size (A) and rate of maturing (k) for body weight, body length and hip height of Brakmas and Bali cows, while calving rate, pre-weaning viability and calf-crop weaned percentage were measured to evaluate the maternal traits. The goodness of fit of the models was determined by the highest coefficient of determination (R2) and the lowest residual mean square (MSE). Logistic model was the best model to determine the mature weight (R2=0.973; MSE=1037.4) and body length (R2=0.993; MSE=81.2) for Brakmas cattle, while von Bertalanffy and Gompertz models were found to be the best models to describe the growth pattern for hip height for this cattle breed as these models had the same coefficient of determination and residual means squares value of 0.997 and 38.3, respectively. The von Bertalanffy model was found to be the best model to describe the growth pattern for body weight, body length and hip height for Bali cattle with the R2 of 0.973, 0.994 and 0.998, respectively, and the MSE of 601.9, 57.7 and 23.7, respectively. Although other competing models also showed a similar value of coefficient of determination,the lowest residual mean square value became the determinant factor. It was also found that every model estimated negative correlation between the mature size and maturing rate, indicating that animals with slower growth will attain its mature size later than fast growing animals. Brakmas cattle showed higher maternal ability compared to Bali cattle in this study. It showed the superiority in calving rate (p=0.0002), pre-weaning survival (p<0.0001) and percentage of calf-crop weaned (p=0.0079). It is also revealed that apart from breed, age of dam become an important source of variation to determine the maternal abilities.